Cohort profile: the Spanish Early-onset Colorectal Cancer (SECOC) cohort: a multicentre cohort study on the molecular basis of colorectal cancer among young individuals in Spain. Issue 12 (30th December 2021) - Perea, Jose; Marti, Marc; Espin, Eloy; Hernandez-Villafranca, Sergio; Orihuela, Pilar; Vidal Tocino, Rosario; Alcazar, Jose Antonio; Vivas, Alfredo; Narvaez, Cristina; Prieto, Isabel; Asensio, Luis; López Rojo, Irene; et al.
Abstract : Purpose: The Spanish Early-onset Colorectal Cancer (SECOC) study is a multicentre prospective cohort established in Spain to investigate the molecular basis of early-onset colorectal cancer (EOCRC), including metabolic alterations. Participants: 220 patients with EOCRC have been enrolled since January 2019 through 18 centres across Spain. Individual-level data were collected by questionnaire, including lifestyle and other colorectal cancer-related factors. Medical record review was performed to capture clinical, histopathological and familial cancer history data. Biospecimen collection (blood, stool, tissue) at diagnosis and at various time points across treatment, as applicable, is also completed. Findings to date: Participants had a median age of 44 years (range 14–49), and the majority are men (60%), with individuals age 40–49 years at EOCRC diagnosis being over-represented. Forty-three per cent of participants were diagnosed with a tumour in the rectosigmoid junction/rectum. Nearly two-thirds of EOCRC cases (64%) were diagnosed with advanced stage (III–IV) disease, and 28% of cases had no reported familial history of cancer. Future plans: We are actively recruiting and observing participants; we plan to administer follow-up questionnaires and perform additional biospecimen collection. This prospective cohort offers a unique, rich resource for research on EOCRC aetiologies and will contribute to larger international efforts to disentangle the rising disease burden.